2006
DOI: 10.4037/ajcc2006.15.5.502
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Length of Stay in the Intensive Care Unit

Abstract: • Background Long stays in the intensive care unit are associated with high costs and burdens on patients and patients’ families and in turn affect society at large. Although factors that affect length of stay and outcomes of care in the intensive care unit have been studied extensively, the conclusions reached have not been reviewed to determine whether they reveal an organizational pattern that might be of practical use in reducing length of stay in the unit. • Objective To identify and catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 56 publications
1
58
0
3
Order By: Relevance
“…Tulloch et al (2011) found female gender to be associated with increased length of stay only in studies with large sample size. Significant association between healthy communication or a stable relationship between patient and caregiver and reduced length of stay has also been found in some studies (Frensch & Cameron, 2002;Gruenberg et al, 2006). In addition, a recent study by Zhang, Harvey, and Andrew (2011) found that lack of social and family support predicted prolonged length of stay.…”
Section: Introductionmentioning
confidence: 67%
“…Tulloch et al (2011) found female gender to be associated with increased length of stay only in studies with large sample size. Significant association between healthy communication or a stable relationship between patient and caregiver and reduced length of stay has also been found in some studies (Frensch & Cameron, 2002;Gruenberg et al, 2006). In addition, a recent study by Zhang, Harvey, and Andrew (2011) found that lack of social and family support predicted prolonged length of stay.…”
Section: Introductionmentioning
confidence: 67%
“…2008), development of renal impairment (Wright et al . 2003) or social factors (Gruenberg et al . 2006, Wright et al .…”
Section: Discussionmentioning
confidence: 99%
“… Length of stay in the intensive care unit. Although multifactorial, any reduction can be associated with monetary savings 12 …”
Section: Methodsmentioning
confidence: 99%